Performance Responses and Fillet Quality of Rainbow Trout (Oncorhynchus mykiss) to Increasing Addition Levels of Dietary Supplementation of Guanidinoacetic Acid - Pedro Henrique Sessegolo Ferzola; Judith Ringel; Elena Beneder; Carsten Schulz; Martin Gierus (Animals)
Guanidinoacetic acid (GAA) plays an important role in cellular energy use and protein synthesis. The objectives of this study were to determine the optimal level of dietary GAA regarding the growth performance and fillet characteristics of rainbow trout (Oncorhynchus mykiss). A total of 300 trout (initial weight, 66.84 ± 7.82 g) were fed isonitrogenous (34%) and isocaloric (20.6 MJ kg−1) diets with increasing levels of GAA (0.00, 0.06, 0.12, 0.18%) for 90 days. The results showed that trout fed GAA (either 0.06, 0.12, or 0.18%) yielded better (p < 0.05) performance (BW, BWG, FCR, and SGR) than trout fed the control diet (0.00% GAA inclusion). No differences (p > 0.05) were observed for BW, BWG, nor FCR among trout fed GAA. Nonetheless, trout fed a diet with a 0.12% GAA inclusion had the highest (p < 0.01) SGR. Fillet quality was not affected by GAA supplementation (p > 0.05) for cook loss, shear force, nor colour. Trout fed 0.06% GAA inclusion tended (p = 0.08) to have a higher WHC. Moreover, trout fed 0.12 and 0.18% GAA had lower (p < 0.05) pH values than trout fed the control diet and 0.06% GAA. Our findings give insights for the growth promotion and fillet quality of trout fed diets supplemented with GAA, especially at the level of 0.12%.